THE EFFECTIVENESS OF THEMATIC TEACHING MATERIALS BASED ON LOCAL WISDOM TO IMPROVE THE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Ester Ester; Surya Dharma; Dede Ruslan (Teunuleh Publisher, 2022)
The purpose of this study is to determine the effectiveness of thematic teaching materials based on local wisdom values in improving the learning outcomes of grade IV students. This research was conducted in elementary school, Palipi district, Samosir regency. This research method is development research. The subjects of this study were grade IV students of Elementary School, Palipi District, Samosir Regency, which totaled 59 people and were divided into 3 classes. The data analysis technique in this study is a descriptive study and t-test of research results and conclusions in this study, namely thematic teaching materials based on the values of local wisdom are categorized as practical because the module of student response response results from trials is limited and large-scale trials have increased. It can be seen that students prefer to use modules in the implementation of free poetry writing learning with an average percentage of Test I student responses of 88.1% and Test II student responses increased by a percentage of 91.9% interested in modules. From these results it can be assumed that if the value is more than 90 then it is categorized very well. If the category is very good, thematic teaching materials based on local wisdom values are practically used in learning.